THE CHILDHOOD AND THE CHILD IN ART AND CULTURAL INDUSTRY: PROBLEM OF EDUCATION? - Oliveira, Paula Ramos de [UNESP]; Badia, Denis Domeneghetti [UNESP]; Fortunato, Ivan (Univ Federal Sergipe, 2020)
The paper discusses the trifold relationship between cultural industry, childhood and education, through a dialogue between these elements. It is highlighted the cultural industry's formula of reducing art to consumer products through a simplification of the imaginary in order to sustain itself and perpetuate the capitalist market. Education emerges as resistance, whereby art must be presented as a form of aesthetic fulfillment, development of creativity and critical thinking, presenting children with other ways of seeing and living the world. It is hoped that the discussion presented here will serve to shed light on the still dominant and insistent presence of the cultural industry in society, imposing itself since childhood, and the need to create resistance to it, under penalty of maintaining the vicious cycle of merchandise-consumption. In this context, education and art are indispensable.
Keywords: Capitalism; Imaginary; Experience